2016
DOI: 10.21315/mjms2016.23.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Canabis-induced Moto-cognitive Dysfunction in Wistar Rats: Ameliorative Efficacy of Nigella Sativa

Abstract: A literature search of related articles was carried out in electronic data sources. Initially, 276 randomised controlled trials related to the title were collected, after which 44 were selected using the keywords. Overlapping articles, articles with a study duration of less than six months, and studies involving young participants were removed from the list. The remaining 20 articles were checked for entitlement using the PEDro scale. A total of nine eligible articles with 1486 participants were analysed. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The fixed brain tissues were cleaned in xylene and processed to obtain paraffin wax embedded in paraffin, refrigerated and sectioned into 5‐μm sections of the hippocampal blocks using arotary microtome (MK 1110), and stained with H and E for general cytoarchitecture following the standard protocol for histology (Imam et al., 2016). Thereafter, stained slides were mounted, and histological evaluation was conducted to observe and analyze the degree of neuromorphological distortions in the hippocampal regions of CA1, CA3, and dentate gyrus of rats treated with lead and/or melatonin using a light microscope (Nikon, Tokyo, Japan) at 400× magnification with an in‐built camera attached to a monitor to produce photomicrographs.…”
Section: Methodsmentioning
confidence: 99%
“…The fixed brain tissues were cleaned in xylene and processed to obtain paraffin wax embedded in paraffin, refrigerated and sectioned into 5‐μm sections of the hippocampal blocks using arotary microtome (MK 1110), and stained with H and E for general cytoarchitecture following the standard protocol for histology (Imam et al., 2016). Thereafter, stained slides were mounted, and histological evaluation was conducted to observe and analyze the degree of neuromorphological distortions in the hippocampal regions of CA1, CA3, and dentate gyrus of rats treated with lead and/or melatonin using a light microscope (Nikon, Tokyo, Japan) at 400× magnification with an in‐built camera attached to a monitor to produce photomicrographs.…”
Section: Methodsmentioning
confidence: 99%
“…For analysis, the trial was performed in a well-illuminated wooden box divided into 4 × 4 squares. It has been reported that avoidance of central squares with preference towards the perimeter areas provides an indication of elevated anxiety levels in the rats [30,31,32].…”
Section: Methodsmentioning
confidence: 99%